2016
DOI: 10.1016/j.physd.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Modulational instability in a PT-symmetric vector nonlinear Schrödinger system

Abstract: A class of exact multi-component constant intensity solutions to a vector nonlinear Schrödinger (NLS) system in the presence of an external P T-symmetric complex potential is constructed. This type of uniform wave pattern displays a non-trivial phase whose spatial dependence is induced by the lattice structure. In this regard, light can propagate without scattering while retaining its original form despite the presence of inhomogenous gain and loss. These constant-intensity continuous waves are then used to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Recent attempts, along this direction, have utilized a rather special complex potential, in which the spatial forms of the real and the imaginary part are functionally related. Under this condition, constant-intensity waves with non-trivial spatially inhomogeneous phase are shown to exist [28,29]. However, this condition restricts the generality of the structure and its potential application in realistic configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Recent attempts, along this direction, have utilized a rather special complex potential, in which the spatial forms of the real and the imaginary part are functionally related. Under this condition, constant-intensity waves with non-trivial spatially inhomogeneous phase are shown to exist [28,29]. However, this condition restricts the generality of the structure and its potential application in realistic configurations.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of δ potential on MI has also been studied via using linear stability analysis [42]. Linear stability analysis has also been studied for MI in nonlinear complex parity-time symmetric periodic potential [43] ,even, for different regimes of threshold [44]. It has also been observed that MI is independent of PT symmetric potential term [45].…”
Section: Introductionmentioning
confidence: 99%